The Relationship of Physical Literacy and Physical Fitness in Physical Education Learning at State Junior High Schools in Bandung City - Yusuf Ferdiansyah; Yudy Hendrayana; Marisa Noviyanti Fajrah Ilsya (Universitas Negeri Semarang, 2025)
The writing of this article aims to analyze the relationship between physical literacy and physical fitness in physical education learning at state junior high school throughout the city of Bandung. The main problem in this study is the low motivation and participation of students in physical activities which has an impact on decreasing the level of physical fitness. This study uses a descriptive quantitative approach with a correlational method. This study involved 281 grade VIII students in three state junior high schools in Bandung City, namely State Junior High Schools 9 Bandung, State Junior High Schools 40 Bandung and State Junior High Schools 50 Bandung with age group 13-14 years old who were selected through cluster random sampling technique. Physical literacy data was collected using a questionnaire instrument (PLAYself) and physical fitness data was measured through the V-Sit and Reach, 60-second Sit Up, 30-second Squat Thrust and PACER Test. Data analysis included the Kolmogorov-Smirnov normality test, the Compare Means (Means) linearity test, and the Spearman’s rho Rank correlation test. The results showed a positive and significant relationship between physical literacy and physical fitness (rs = 0.176, p = 0.003). These results indicate a positive correlation between physical literacy and students physical fitness. Although this correlation is very weak, these findings demonstrate that physical literacy remains a crucial component in supporting physical fitness improvement through physical education provided in schools. Thus, it is nesessary to have physical education learning that is oriented towards the development of comprehensive physical literacy.